Organization of sports and recreational tourism in the city of Valjevo - Selenić Uroš; Gavrilović Ana (Ekonomija: teorija i praksa, 2023)
The subject of the work was sports and recreational tourism to highlight the current and new opportunities for the development of a selective form of tourism in Valjevo. The focus was on providing a high-quality description and presentation of the tourist and sports infrastructure, existing offers of sports and recreational facilities, and events in this city. The methods of observation, interviews, and document analysis, with a specific emphasis on the analysis of websites and historical research, were used in the preparation of the paper. The conclusion is that Valjevo has sports clubs, thanks to which there is the possibility of recreation and visiting various events during the stay of tourists in this city. However, the main hindrances to the development of a selective form of tourism are accommodation facilities and outdated sports infrastructure.